LEARNERS’ ENGAGEMENT WITH TEACHER WCF OR LEARNERS’ ENGAGEMENT WITH PEER WCF? LEARNERS’ PERSPECTIVES. - Nirwanto Maruf; Indyra Mahdiana; Bahar Bahar (British : Jurnal Bahasa dan Sastra Inggris, 2022)
Written corrective feedback (WCF) is defined as some responses related to learners’ linguistic errors in written and used by teachers to help learners for improving their writing’s accuracy. It is necessary to understand regarding learners’ engagement with corrective feedback. By understanding learners’ engagement with written corrective feedback, teacher can determine the appropriate type of written corrective feedback which used as effective strategy in improving learners’ writing ability. This study aims to reveal learners’ perspectives on their engagement with written corrective feedback and learners’ engagement with peer written corrective feedback (WCF). This quantitative research obtained the data through questionnaires. These questionnaires aim to measure both learners’ engagement with teacher written corrective feedback and learners’ engagement with peer written corrective feedback. The results of the study indicate that learners are more engage and agree with teacher WCF practice (mean 35.5), rather than engagement with peer WCF practice (mean 30.8) since teacher WCF had greater positive impact for learners’ writing rather than peer WCF. This researches conclude that learners believe that teacher WCF more useful to locate their errors. Meanwhile, related to peer WCF, learners engage in affective by feeling happy, enthusiastic, and interested in receiving and reading peer WCF.